2018
DOI: 10.1111/cei.13200
|View full text |Cite
|
Sign up to set email alerts
|

Serum exosomes of chronic gastritis patients infected withHelicobacter pylorimediate IL-1α expression via IL-6 trans-signalling in gastric epithelial cells

Abstract: Emerging evidence has linked the exosomes to many immunological disorders, including infectious diseases. However, knowledge regarding the role of exosomes in Helicobacter pylori infection is limited. Here, we show that serum exosomes from chronic gastritis patients with H. pylori infection (Hp exosomes) stimulate the expression of the soluble interleukin (IL)-6 receptor (sIL-6R), which is involved in IL-6 trans-signalling in gastric epithelial cells. Interestingly, sIL-6R up-regulates expression of the proinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…10 This observation, together with the fact that H pylori strains lacking a T4SS also cause inflammation, suggests that other mechanisms must be involved in H pylori-induced inflammation. 13 IL-6 mainly exerts its effects through the membrane-bound gp130 receptor, resulting in the activation of signal transducer and activator of transcription 3 (STAT3) signaling which has important functions in cell growth and apoptosis. These bacterial membrane vesicles enter epithelial cells and carry a range of immunomodulatory factors that are likely to regulate host inflammation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10 This observation, together with the fact that H pylori strains lacking a T4SS also cause inflammation, suggests that other mechanisms must be involved in H pylori-induced inflammation. 13 IL-6 mainly exerts its effects through the membrane-bound gp130 receptor, resulting in the activation of signal transducer and activator of transcription 3 (STAT3) signaling which has important functions in cell growth and apoptosis. These bacterial membrane vesicles enter epithelial cells and carry a range of immunomodulatory factors that are likely to regulate host inflammation.…”
mentioning
confidence: 99%
“…11,12 Additionally, it was recently shown that host-derived EVs in the serum of H pylori-infected subjects induced the expression of the soluble interleukin (IL)-6 receptor (sIL-6R) in gastric epithelial cells, leading to upregulation of the pro-inflammatory cytokine interleukin-1α (IL-1α). 13 IL-6 mainly exerts its effects through the membrane-bound gp130 receptor, resulting in the activation of signal transducer and activator of transcription 3 (STAT3) signaling which has important functions in cell growth and apoptosis.…”
mentioning
confidence: 99%
“…Analyses of a PPI network showed that CAT, IL-6, IL-1b, and VEGFA were the most correlated proteins, followed by PTGS2. In combination with analyses of enrichment of GO pathways and KEGG pathways, we believe that the mechanism of action of AMK in CG treatment is closely related to inflammation regulation (Graham et al, 2000;Bartchewsky et al, 2009;Chen et al, 2018). For example, the target symbol PTGS2 (also named cyclo-oxygenase (COX)-2) can be associated with 18 active ingredients in AMK which can affect the IL-17 signaling pathway, TNF signaling pathway, and C-type lectin receptor signaling pathway and, thus, the regulation of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…30 Furthermore, exosomes isolated from the serum of patients exhibiting a chronic gastritis and have H. pylori infection can induce expression of the soluble IL-6 receptor, which increases IL-1α expression, in gastric epithelial cells. 31 It has been reported that Mycobacterium tuberculosis-infected macrophages release extracellular vesicles including exosomes that can deliver pathogen-associated molecular patterns (PAMPs), such as mycobacterial proteins, lipids, and nucleic acids, to naïve macrophages, activating or inhibiting immune responses. 23,[32][33][34][35] Moreover, exosomes from Mycobacterium tuberculosis-infected macrophages or from the serum of Mycobacterium tuberculosisinfected mice can activate endothelial cells, suggesting a role for these exosomes in promoting leukocyte adhesion and cell migration as well as inflammation upon Mycobacterium tuberculosis infection.…”
Section: Discussionmentioning
confidence: 99%